1999
DOI: 10.1007/s001150050399
|View full text |Cite
|
Sign up to set email alerts
|

Das Konstrukt Lebensqualität Metaanalytische Validierung und die Entwicklung eines modularen Erhebungssystems

Abstract: The construct Quality of Life (QoL) is investigated by metaanalysis of eight (inter)nationally validated questionnaires in a multicenter study. Data have been collected in a mentally healthy (n = 479), a depressed (n = 171) and a schizophrenic (n = 139) sample. Conventional psychometric criteria and a facet analytical methodology have been applied. The resulting questionnaire "Modular System for Quality of Life" (MSQoL) consists of a core module with 47 items (one "G-factor" and six subdimensions), which is su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Quality of life during the past 4 weeks was evaluated using the core module of the Modular system for quality of life (MSQoL, [44]). …”
Section: Methodsmentioning
confidence: 99%
“…Quality of life during the past 4 weeks was evaluated using the core module of the Modular system for quality of life (MSQoL, [44]). …”
Section: Methodsmentioning
confidence: 99%
“…Other studies however indicate that measures of subjective and objective QoL assess different constructs [4], and discrepancies between subjective and objective QoL, even though of a lesser magnitude, has also been shown for other psychiatric patient groups [2]. Studies show good test–retest reliability for psychotic patients' self-reported QoL [34,37] and demonstrate that patients with schizophrenia construct QoL very similar to healthy controls and to patients with depression [34]. It is thus reasonable to conclude that self-reported satisfaction or subjective QoL also is an important and valid outcome measure in schizophrenia and other psychotic disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Das Konstrukt der Lebensqualität hat sich in theoretischen Analysen als valide erwiesen [21].Wir wählten zur Querschnittsuntersuchung die deutsche Kurzversion des entsprechenden WHO-Instruments, des WHOQOL-BREF [26],der vielfach zur Untersuchung physisch Kranker und gesunder Probanden, aber auch psychisch kranker Menschen verwendet wurde [2,7].Der WHOQOL-BREF liefert Zufriedenheitswerte bezüglich 4 Domänen: physische und psychische Befindlichkeit, soziale Beziehungen und Umwelt sowie eine Selbstbeurteilung zur allgemeinen Lebensqualität und Gesundheit. Die Antworten auf die einelnen Fragen wurden in 5 Graden erfasst: 1 (sehr unzufrieden) bis 5 (sehr zufrieden).…”
Section: Messung Der Lebensqualitätunclassified